Los tropos de la música - Beeman, William O. (Revista de Antropología Social, 2006)
Although tropic structures are generally linked to verbal or visual materials in culture, tropes have long been understood as primary devices in the production of music. This paper seeks to show how musical tropes affect the interpretation of musical materials by listeners. Tropes in music will be shown to correspond to the principal semiotic functions observed in traditional linguistics: iconic, indexical and symbolic. Using audio materials, this essay explore a number of these musical tropes taken from traditional Asian and Native American music; and Western art music from Baroque, Classical and modern periods. Iconic functions are shown to include onomatopoeic musical structures. Indexical functions involve internal imitation, repetition and restatement, and symbolic functions involve the use of sound materials evocative of specific cultural images or institutions. The paper finally suggests that linguistic, visual and musical tropes are interconnected, mutually reinforcing, and may stem from the same set of cognitive functions in human culture.
Keywords: Musical tropes; Musical mediation; Firstness; Secondness; Thirdness; Iconicity; Indexicality; Symbolic association and tropic reinforcement